TRANSLATION, WHY IS THIS DIFFICULT? STUDENTS’ DIFFICULTIES IN TRANSLATING ENGLISH TEXT - Dyah Sih Pratiwi; Candraning Prihatini (Journal of English Education and Linguistics, 2022)
The purpose of this research was to describe the difficulties in translating text, the type of error in translation and the factors cause it in translation at Muhammadiyah Lampung University Students. The subject of this research were Muhammadiyah Lampung University at fourth semester in English Education Department. The data collecting technique of this research used test and questionnaire. The result of this research indicated that students have some difficulties in Translation Subject such as (1) Elliptical Error (12%), Idioms (57%), and textual meaning ( 31%). Based on the data the majority students indicated that Idioms is the most difficulties in Translation English Text.